Prognostic Characterization of Higher-Grade Meningiomas: A Histopathological Score to Predict Progression and Outcome - Bertero, Luca (J Neuropathol Exp Neurol, 2019)
Higher-grade meningiomas (WHO grade II and III) represent a diagnostic and prognostic challenge. We assessed the pathological and molecular characteristics of 94 higher-grade meningiomas (85 grade II, 9 grade III) to identify novel prognostic parameters. Higher mitotic count (p = 0.018), diffuse (≥50%) prominent nucleoli (p < 0.001), and sheeting (p < 0.001) were associated with recurrence. Lower SSTR2a-positive cells median rate (p = 0.048) and TERT promoter mutations (p = 0.014) were associated with recurrence and patient death, respectively; further analyses did not identify other outcome associations. Presence of Ki67 hot spots was associated with a shorter progression-free survival (PFS), independently of WHO grade at multivariate analysis (HR = 3.35, p = 0.008). Necrosis was related to a poorer overall survival (OS) at univariate (focal: HR = 4.55, p = 0.041 and diffuse: HR = 7.38, p = 0.020) and Kaplan-Meier analyses. A prognostic score was designed based on previous results: Presence of diffuse (≥50%) prominent nucleoli (0/1 point), diffuse (≥50%) sheeting (0/1 point), focal (<50%) or diffuse (≥50%) necrosis (0/1/2 points), and Ki67 hot spots (0/1 point). A total score ≥4 predicted poorer PFS and OS by Kaplan-Meier (PFS: 1.7 vs 6.4 years, p < 0.001 and OS: 5.2 vs 10.8 years, p = 0.001) and multivariate (PFS: HR = 5.98, p < 0.001 and OS: HR = 2.99, p = 0.048) analyses. These results were confirmed in an independent series of 58 grade II meningiomas (PFS: HR = 7.22, p = 0.002 and OS: HR = 9.69, p = 0.003). These associations and the integrated score could complement WHO grading.